2016
DOI: 10.1088/0022-3727/49/27/275103
|View full text |Cite
|
Sign up to set email alerts
|

Insulator-to-metal transition in vanadium supersaturated silicon: variable-range hopping and Kondo effect signatures

Abstract: We report the observation of the insulator-to-metal transition in crystalline silicon samples supersaturated with vanadium. Ion implantation followed by pulsed laser melting and rapid resolidification produce high quality single-crystalline silicon samples with vanadium concentrations that exceed equilibrium values in more than 5 orders of magnitude. Temperature-dependent analysis of the conductivity and Hall mobility values for temperatures from 10 K to 300 K indicate that a transition from an insulating to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…All these results are in agreement with time of flight secondary ion mass spectrometry (ToF-SIMS) measurements and high-resolution transmission electron microscopy (HR-TEM) images of similar samples reported previously [25]. In this sense, ToF-SIMS showed that both samples present a vanadium concentration higher than the theoretical limit to obtain an IB material.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…All these results are in agreement with time of flight secondary ion mass spectrometry (ToF-SIMS) measurements and high-resolution transmission electron microscopy (HR-TEM) images of similar samples reported previously [25]. In this sense, ToF-SIMS showed that both samples present a vanadium concentration higher than the theoretical limit to obtain an IB material.…”
Section: Resultssupporting
confidence: 92%
“…As we have recently shown [25], these V-supersaturated Si samples have electrical transport properties that confirmed the insulator-to-metal transition and the formation of an IB in a high quality material. Since spectral photoconductance is directly related to the absorption coefficient [44], we suggest that the intense sub-bandgap photoresponse of the V supersaturated Si samples, together with the presence of abrupt photoresponse edges is consistent with optical transitions from the VB to the IB and from the IB to the CB.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…3(c) , the reduced activation energy W is nearly zero for the sample PLA-1.2 × 10 16 cm −2 . This means that it exhibits a relatively finite conductivity as temperature tends to zero 34 . The decrease of W at low temperatures for the sample PLA-1.2 × 10 16 cm −2 indicates that this sample lies in the metallic regime.…”
Section: Resultsmentioning
confidence: 99%
“…Single-crystalline silicon layers with transition metals (Ti, V, Au, and Ag) or chalcogens (S, Se, and Te) at concentrations above 10 19 cm -3 have been obtained by means of ion implantation and subsecond annealing techniques (in a process denominated as supersaturation or hyperdoping). We have shown that silicon hyperdoped with Ti [9,10] or V [11] presents outstanding properties such as a sub-bandgap optical absorption coefficient in the 10 4 cm -1 range [12] or a photoconductive response extended down to 0.2 eV (6.2 µm) at cryogenic temperatures. [13] Gold hyperdoped [14,15] or silver hyperdoped [16] This work deepens the understanding of the optoelectronic mechanisms ruling hyperdoped-based photodevices and shows the potential of Ti hyperdoped-Si as a fully complementary metal-oxide semiconductor compatible material for room-temperature infrared photodetection technologies.…”
mentioning
confidence: 99%